Autonomous hydrogen systems: control strategy - Martins, João F. (2010)
This paper describes the control strategy for a Stand-Alone Energy System Supported by Totally Renewable Hydrogen Production. The basic control strategy considers the pressurized hydrogen gas storage as the energy buffer. The basic logic is that the exceeding renewable energy (solar and wind) is used to accumulate hydrogen, while the fuel cell uses this hydrogen to produce electrical energy within insufficient solar/wind energy. The system is completely autonomous, conceived for off-grid operation. It is composed by solar panels and a wind turbine as primary energy converters, hydrogen tanks as energy buffer and a fuel-cell and an electrolyzer as secondary energy converters.